Success: From failure to failure with enthusiasm - Gabryś-Barker, Danuta (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2014)
In this article I would like to look briefly at the background to the concept of enthusiasm, its evolution from earlier understandings in the domain of religion to its modern understandings as expressed by various lexicographic sources. This will lead me to the major focus of the article, which is the various applications of enthusiasm in education. Not surprisingly, there is a large body of empirical studies on teacher and learner enthusiasm and its contribution to successful teaching and learning. A selection of studies is presented here and their results are discussed. The empirical part of this article looks at my own qualitative study of pre-service EFL teachers’ narratives and their perceptions of teacher enthusiasm and its impact on teaching and learning success, as seen from their own perspective. In the concluding part I suggest how teacher training should incorporate ideas on teacher enthusiasm and strategies to deploy them as prospective weapons in preventing professional burnout in teachers. As Churchill said, “success is not final . . . Failure is not fatal . . . it´s the courage to continue that counts.” I strongly believe that it is enthusiasm that gives us courage to continue.
Keywords: teacher enthusiasm, enthusiasm indicators, enthusiasm effective- ness, learner achievement, affectivity, teacher training, pre-service teachers